Optimization of optical uniformity factors of backlight module using robust design method - Wang, Ju-Chi; Fan, Yu-Cheng; Fang, Te-Hua; Tran, Anh-Son; Cheng, Yu-Ting (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
In order to meet the advent of the high-definition liquid crystal display (LCD) era, in addition to the high-quality panel manufacturing technology, how the backlight module can provide a uniform backlight with higher uniformity for a better experience in viewing, is a very important and urgent issue. In this study, the 15.6-inch side-in backlight module was used as the benchmark, and the Taguchi method was applied to find the high uniformity. The matching of the fishbone diagram affects the optical uniformity factor of the backlight module, such as the size of the light guide plate dot, the color of the plastic frame, the color of the fixed gel of the light guide plate, and the difference of the reflection surface. The optical analog software LightTools is used according to the orthogonal table. The signal-to-noise (S/N) ratio of the average uniformity characteristics is obtained, then it is converted into the best response factor of the factor response table and the factor reaction diagram. The homogeneity at 13 points is as high as 90.12%, which is 4.72% higher than the original design factor. The contribution of the four factors to the uniformity can be obtained by using the variance analysis. Finally, the influence of each factor level on the uniformity is discussed.
Optica Applicata, Vol. 52, 2022, nr 1, s. 5-20
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; backlight module; uniformity; Taguchi method; LightTools